AVALIAÇÃO DA EFICIÊNCIA ENERGÉTICA DE MATRIZES NELORADAS NA FAZENDA UEMS - SANTOS, Marrony Gonçalves Pires; FERNANDES, Henrique Jorge; BEZERRA, Thais dos Santos; SILVA, Gislaine Jara; SILVA, Camila de Souza; TEIXEIRA, Edvan Correia (ANAIS DO ENIC, 2024)
-